Czy istniała instytucja opozycji politycznej w demokracji bezpośredniej? (analiza demokracji ateńskiej i republiki rzymskiej) - Nieć, Mateusz (Polityka i Społeczeństwo, 2020)
The article, based on works Ancient historian and Classicists, presents direct democracy in the Ancient World. The author is looking for an example institution of oppositions in contemporary political system, especially the electoral system. In his opinion, the institution of oppositions was hidden within the electoral systems of Athens and Rome.